A Coupled Lattice Boltzmann-Volume Penalization for Flows Past Fixed Solid Obstacles with Local Mesh Refinement. (29th January 2018) - Guo, Kai; Cui, Xiongwei; Liu, Minghao
Abstract : A coupled Lattice Boltzmann-Volume Penalization (LBM-VP) with local mesh refinement is presented to simulate flows past obstacles in this article. Based on the finite-difference LBM, the local mesh refinement is incorporated into the LBM to improve computing efficiency. The volume penalization method is introduced into the LBM by an external forcing term. In the LBM-VP method, the processes of interpolating velocities on the boundaries points and distributing the force density to the Eulerian points near the boundaries are unnecessary. Performing the LBM-VP on a certain point, only the variables of this point are needed, which means the whole procedure can be conducted parallelly. As a consequence, the whole computing efficiency can be improved. To verify the presented method, flows past a single circular cylinder, a pair of cylinders in tandem arrangement, and a NACA-0012 are investigated. A good agreement between the present results and the data in the previous literatures is achieved, which demonstrates the accuracy and effectiveness of the present method to solve the flows past obstacle problems.